ANALISIS MANAJEMEN BISNIS SYARIAH KOPERASI UNIT DESA KARTINI MANDIRI LESTARI DESA PASAREAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT PEDESAAN - Herawati, Alda; Kusumaningrum, Ria; Melinasari, Susi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Kartini Mandiri Lestari Cooperative which is a cooperative supported by the Damandiri Foundation which seeks to increase the utilization of the Modal Kita business unit to help the economy of the residents of Smart Mandiri Lestari Village (DCML) Pasarean Pamijahan Bogor, West Java. The current progress of cooperatives can be seen from the development of remaining business results which continue to increase every year. The Kartini Mandiri Lestari Village Unit Cooperative can improve community welfare, as proven by the existence of programs that have succeeded in improving community welfare. This research is field research with the type of research being qualitative research with a descriptive analysis approach. Data collection techniques use observation, interviews and documentation. Data analysis was carried out by data reduction, presentation and then drawing conclusions. The implementation of the management of the Kartini Mandiri Lestari Village Unit Cooperative in an effort to improve community welfare is considered good as evidenced by the implementation of good cooperative management. Cooperative management consists of member meetings, management and supervisors. The appropriate management processes implemented by the Village Unit Cooperative are planning, organizing, implementing and supervising. The effect of good Village Unit Cooperative management is that the community experiences increased welfare.